Noise reduction of automobile cooling fan based on bio-inspired design. (February 2021) - Wang, Shuwen; Yu, Xinke; Shen, Lixia; Yang, Ailing; Chen, Eryun; Fieldhouse, John; Barton, David; Kosarieh, Shahriar
This study aims to minimize the noise generated by automobile cooling fans. Fan blade structures with ridged surfaces based on bio-inspired principles are 3D printed and used to replace the conventional fan blades. The effect of the bio-inspired ridge structures on the noise reduction of the cooling fan is demonstrated by orthogonal experiments in a semi-anechoic chamber. Experimental results show that with an increase in the rotational speed, the effect of the surface textures on the acoustic performance of the cooling fan becomes more significant. For example, at a fan speed of 1750 r/min, all the bio-inspired blade designs reduce noise compared with the original fan and, in particular, the sound pressure level is reduced by 3.83 dB(A) for the design with a ridge width of 4 mm and a ridge pitch of 15 mm. Through variance analysis of the measured noise, the ridge pitch distance has the most significant impact on noise reduction under low speed conditions whilst, under high speed conditions, the ridge width has the most significant influence. In addition to the experimental studies, computational fluid dynamics (CFD) simulations of the cooling fan are carried out to explain the mechanism of noise reduction for the ridged fan blades. When the fan runs, the horseshoe vortexes generated by the ridge structures disturb the flow of the boundary layer, reduce the influence of the fluid flow on the boundary layer, and delay the transition of the fan blade laminar flow to turbulence. It is also seen that there is a reduction of the intensity of the fan blade trailing edge vortices and the scale of the secondary vortices, thereby achieving the overall aim of noise reduction. This research has significance in the noise reduction design of automobile cooling fans.